2019
DOI: 10.1002/chem.201804721
|View full text |Cite
|
Sign up to set email alerts
|

Sliding Polymeric Layers and Anion Displacement Coupled with Spin Crossover in Two‐Dimensional Networks of [Fe(hbtz)2(CH3CN)2](BF4)2

Abstract: The abrupt high spin (HS)→low spin (LS) transition (T↓1/2=136 K) in [Fe(hbtz)2(CH3CN)2](BF4)2 (hbtz=1,6‐di(tetrazol‐2‐yl)hexane) is finished at 100 K and further thermal treatment influences the spin crossover. Subsequent heating involves a change of the spin state in the same way (T↑1/2=136 K) on cooling. In contrast, cooling below 100 K triggers different behavior and T↑1/2 is shifted to 170 K. The extraordinary structural changes that occurred below 100 K are responsible for the observed diversity of proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 94 publications
1
6
0
Order By: Relevance
“…Overall, the SCO character is sharpened upon further thermal cycles and the anomaly between 215–230 K in the heating curve is reduced. Changes to magnetic susceptibility traces with thermal cycling have been reported on several occasions and can occur due to sample changes over cycling (such as desolvation) or related to order/disorder phase transitions of components such as anions . Here, we confirm that the changes are not due to desolvation with cycling as the sample was contained in a sealed vessel and the reported features are reproducible over several measurements and samples.…”
Section: Discussionsupporting
confidence: 81%
“…Overall, the SCO character is sharpened upon further thermal cycles and the anomaly between 215–230 K in the heating curve is reduced. Changes to magnetic susceptibility traces with thermal cycling have been reported on several occasions and can occur due to sample changes over cycling (such as desolvation) or related to order/disorder phase transitions of components such as anions . Here, we confirm that the changes are not due to desolvation with cycling as the sample was contained in a sealed vessel and the reported features are reproducible over several measurements and samples.…”
Section: Discussionsupporting
confidence: 81%
“…Additionally, 1,6‐di(tetrazol‐2‐yl)hexane (hbtz) shows the tendency to form topologically identical 2D polymeric systems [Fe(hbtz) 2 (RCN) 2 ](ClO 4 ) 2 (R=CH 3 , [38] C 2 H 5 , C 3 H 5 [40] ) independently of the type of coordinated nitrile molecule. The same topology also occurs for tetrafluoroborate analogs [41] . The exceptional properties are shown by the acetonitrile derivative [Fe(hbtz) 2 (CH 3 CN) 2 ](BF 4 ) 2 for which the structural phase transition is accompanied by an unprecedented large shift of the polymeric layers at distances above 4 Å as well as by relocation of anions.…”
Section: Introductionmentioning
confidence: 67%
“…[33] In contrast, application of other 1,w-di(azolyl)alkanes allowed us to preparet wo-(2D) [34,35] and three-dimensional (3D) [36] coordination polymers of different topologies. At the same time, it was found that 1,w-di(azolyl)alkane-type ligands can also form iron(II) complexes in which the first coordination sphere involves four tetrazolyl, [37][38][39][40][41] or four 1,2,3-triazolyl [30,31,42] rings, and two axially coordinated nitrile molecules. These complexes display thermally induceds pin crossover as well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many examples of anion order‐disorder transitions showing abrupt and hysteretic SCO are known [19–22] . A special case involves anion displacement with a relative shift of cationic Fe‐based layers that leads to an extra stabilization of the LS structure [23] . Less frequent is the study of anion conformational changes.…”
Section: Introductionmentioning
confidence: 99%